The Devil's Punchbowl - Iles, Greg (New York : Scribner, 2009)
A deep river pit in Natchez, Mississippi, reputed to be the hiding spot for Jean Lafitte's hidden treasure and a dumping ground for numerous murder victims, becomes the site of a dangerous showdown for Penn Cage.